Analysis of Third Party Logistic Service in Indonesia - Adhana, Defay Muda; Rivani, Rivani; Hendriyani, Chandra (Universitas Pendidikan Indonesia, 2023)
The growth of the business world has encouraged the rapid development of the logistics business. To increase competitiveness, companies focus a lot on their core business in order to fulfill customers' desires and expectations, so the company started using Third Party Logistics (TPL) to increase the company's sustainability. The aim of this research is to find out how TPL services are in Indonesia. The research method used is qualitative research with a descriptive approach. The research results show that of the 8 best TPL companies in 2022, namely Kamadjaja, Agility, Ceva, DB Schenker, Siba Surya, Puninar, Pancaran, and Deliveree, all of them have implemented types of logistics services in the form of transportation, warehousing, custom service, freight finance service, IT Support, product support, and logistics management and all companies are included in the Customer Developer category where the company takes full care of their needs. For further research, the author suggests further research related to development into the next generation of logistics providers.